Literature Study: The Effect of Problem Based Learning (PBL) on Critical Thinking Ability - Nadia Rahmantika; S.T.Y Slamet; Idam Ragil Widianto Atmojo (Social, Humanities, and Educational Studies (SHES): Conference Series, 2024)
The purpose of this study was to describe the Problem Based Learning (PBL) model on students' critical thinking skills. The method used is qualitative through literature study. The research was conducted through the data collection stage from literature sources. The data that has been obtained is then analyzed using the descriptive analysis method. The Problem Based Learning (PBL) learning model is learning by providing a problem in real daily life to be studied by students so that the right solution can be found in solving it. The results showed that the application of the Problem Based Learning (PBL) model can have a positive influence on students' critical thinking skills. The PBL learning model is considered effective in developing students' thinking skills. This learning model raises curiosity and increases motivation so that it can develop higher thinking skills, especially in critical thinking